Molecular characterization of Mosaic Virus from the cocoa trees showing mosaic symptoms in Yogyakarta, Indonesia - Wiwit Probowati; SUSAMTO SOMOWIYARJO; SEDYO HARTONO (Society for Indonesian Biodiversity, 2019)
Abstact. Probowati W, Somowiyarjo S, Hartono S. 2019. Molecular characterization of Mosaic Virus From the cocoa trees showing mosaic symptoms in Yogyakarta, Indonesia. Biodiversitas 20: 3698-3704. Indonesia is the world's second-biggest producer of cacao after Ivory Coast with its cacao plantations spreads over 1,652 million hectares and mostly managed by smallholders. Cacao as a beneficial commodity can provide job opportunities for over 1.64 million people, with its contribution of more than US- 1.6 billion/year to national income. However, pest and disease infections are inevitably common constraints for the cacao cultivators. One current disease is caused by Cacao Swollen Shoot Virus (CSSV). Despite its noticeable symptoms on the cacao trees suffering from the disease, the knowledge on both the virus existence and the prevention steps in dealing with it is lacking. The information on the diversity of mosaic virus will help us to comprehend its epidemiologic development and the needed countermeasures, as well as its evolution. This research is intended to study the mosaic disease virus molecularly, the virus was obtained from DR1 clones from Kalibawang cacao plantation in Kulon Progo, Yogyakarta. The virus morphology was observed using a transmission electron microscope applying quick dipping method. The PCR analysis with conserved region ORF1 primers was conducted to detect the viral existence in the infected trees. The identification of CSSV molecular characters was undertaken using PCR sequencing analysis which was then examined using BioEdit and Mega5 programs to initiate a relationship dendrogram. The result showed that the DR1 cacao tree clones from Kalibawang were infected by mosaic virus with mild visual severity of leaf typical symptom. From the electronic microscope observation, a ±100 nm rod-shaped viral particle with a diameter of 15.3 mm was found. On the molecular level, the cause of mosaic symptom has CSSV amplified at conserved regions with size 375 bp. The results are the first report confirming that the molecular cause of cacao mosaic disease in Indonesia is CSSV. The molecular characters of CSSV in Yogyakarta are very different from those found abroad.